El retorno a la presencialidad y el impacto en los procesos de enseñanza en Educación Inicial. - Mendoza Torres, Yaleni Alexandra (2022)
The pandemic caused a great impact worldwide, affecting several personal, economic and especially in education scenarios, therefore, this research refers to diagnosing the impact of the return to pre-specialty in the teaching-learning process in education and how it affected in initial education, both students and teachers, the study was carried out in the "Ramón Barba Naranjo" Educational Unit, located in the province of Cotopaxi in the city of Latacunga Zone 3, the research was carried out in the first year of preparatory and initial II, is made up of children from 3 to 5 years old, on the other hand, the basic modality of the research is bibliographic and field which occupies an important place in our study, since it guarantees the quality of the theoretical foundations Of the investigation; the approach of this project is mixed, qualitative-quantitative, having an informative impact, our research has used descriptive statistics in which instruments such as interview and survey were used, which was applied to parents and teachers of the Unit Educational. In summary, education changed, overnight schools closed and all began to use technological means, it was also observed that the vast majority of children failed to understand what teachers taught in virtual classes, both with the help of the parents as the strategies that the teachers applied were not enough for the children to have a meaningful learning, for which the authorities decided to return to the presence voluntarily with the biosecurity measures, because the families did not have technological means and neither with internet access causing a deficit in children's learning, they were inclined to a progressive return.